Blood Clotting Activities of Thrombolytic Agents with Special Reference to a Hageman-like Effect - Iatridis, Sotirios G.; Wilson, Ella Gray; Ferguson, John H.; Rierson, Herman A. (Thrombosis and Haemostasis, 1961)
Representatives of modern thrombolytic agents have been shown to possess certain in vitro clot accelerating activities, which a variety of experiments indicate to be due to a ‘Hageman-like’ effect. This activity is surface dependent and remarkably resistant to long keeping (in active plasmin) and to acid heating, unlike ‘surface factor’ (‘activation product’). The effect is quite powerful under certain test conditions, but it remains to be seen whether it is of any significance during the use of thrombolytic agents therapeutically.